Pengaruh Layanan Perpustakaan Berbasis Inklusi Sosial terhadap Peningkatan UMKM dengan Menggunakan Model TQM di Dinas Perpustakaan dan Kearsipan Kabupaten Dharmasraya - Fadila, Amelia; Nabila, Jeihan (ARZUSIN, 2024)
The purpose of this study was to describe how the influence of social inclusion-based library services on improving umkm using the tqm model at the Library and Archives Service of Dharmasraya Regency. The type of research used is quantitative research with a descriptive approach. The population in this study were umkm actors and resource persons/participants who had participated in social inclusion program training activities at the Dharmasraya Regency Library and Archives Office, namely 378 people. The sampling technique used was simple random sampling. The number of samples in this study were 80 samples using the Slovin formula with a precision of 10%. In this study, researchers used a questionnaire as an instrument. The data collection technique was carried out by distributing questionnaires to all research samples with data analysis techniques including normality test, correlation test, linearity test, T test, and coefficient of determination test. The results showed that social inclusion services had a positive and significant effect on increasing umkm. The social inclusion variable (X) has an influence on increasing umkm (Y) by 59.7% while the remaining 40.3% is influenced by other factors not examined in this study.